2012
DOI: 10.1002/eat.22068
|View full text |Cite
|
Sign up to set email alerts
|

Caregiving and coping in carers of people with anorexia nervosa admitted for intensive hospital care

Abstract: The data indicate that professional and social support alleviates carer distress and may be of particular value for partners who are more isolated than parents. The data also suggest that time spent with practical support may be of more value than emotional support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
56
2
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(67 citation statements)
references
References 60 publications
(36 reference statements)
7
56
2
2
Order By: Relevance
“…Anastasiadou et al, 2014;Hibbs et al, 2014;Raenker et al, 2013), carers of people with ED need more support from services to understand ED, to reduce their perception of guilt and caregiver burden, provide them with hope, and help develop the skills to interact with their care recipient. The current research adds support to this area and also suggests that services need to look at specific demographics of carers (i.e.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Anastasiadou et al, 2014;Hibbs et al, 2014;Raenker et al, 2013), carers of people with ED need more support from services to understand ED, to reduce their perception of guilt and caregiver burden, provide them with hope, and help develop the skills to interact with their care recipient. The current research adds support to this area and also suggests that services need to look at specific demographics of carers (i.e.…”
Section: Discussionmentioning
confidence: 98%
“…A review of previous research indicated that a number of factors may influence carer well-being when caring for an individual with an ED, e.g. perceived level of burden (Gonzalez et al, 2012); being the primary caregiver (Sepúlveda et al, 2012); amount of contact time (Raenker et al, 2013) and gender of the caregiver (Kyriacou et al, 2008b). There was not a measure already in place to capture this information.…”
Section: Methodsmentioning
confidence: 97%
See 2 more Smart Citations
“…It is provided to people with AN by parents, carers and partners. The analysis of data collected in the CASIS study (see Chapter 6) shows that up to three-quarters of carers spent nearly a full day per week providing ED-related care, 406 with potential impacts not only on their health and well-being but also on their capacity to engage in paid employment.…”
Section: Resultsmentioning
confidence: 99%